Status analysis of quality control of administered infusion solution with cytotoxic drugs - Wang, Shan; Zhang, Feng-Ying; Dou, Xue; Pan, Xiao-Lin; Su, Chen; Tian, Jin-Lei; Mu, Dian-Ping (Oncology Reviews, 2025)
Administered infusion solution is a sterile preparation that can be used directly for intravenous infusion of patients by mixed one or more intravenous drugs through aseptic operation technology. Pharmacy intravenous admixture service (PIVAS) center is a professional technical service department of hospital and administered infusion solution of inpatient mostly prepared in PIVAS. During the process of dissolution, dilution, preparation, storage, and use of intravenous drugs, the quality control of administered infusion solution can be affected by various factors. At present, there are no relevant standards and guidance documents for the quality control of administered infusion solution. Cytotoxic drugs are still the main treatment for cancer patients, and mainly prepared in PIVAS in most hospital. We mainly focused on the cytotoxic drugs quality control of administered infusion solution in the paper, and explored associated factors (diluent, container, concentration, temperature, light), physical stability (visual appearance, pH, osmolality, particulate matter), chemical stability (content) and biological stability (sterility). Almost all the literatures in this paper have insufficient data on the related factors and physicochemical stability of the administered infusion solution. Less research has been done on the sterility of administered infusion solution, with only one article involved in this. The cytotoxic drugs administered infusion solution quality control is vital to ensure the safety of drug administration for cancer patient, so it is very important to enhance associated research. This article summarized the relevant literature on the quality control of cytotoxic drugs administered infusion solution, and provided a reference for safer and more efficient use of cytotoxic drugs in clinical practice.